2002
DOI: 10.1111/j.1348-0421.2002.tb02761.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Immunoglobulin Enriched Bovine Colostrum against Oral Challenge with Enterohaemorrhagic Escherichia coli O157:H7 in Mice

Abstract: An immunoglobulin enriched bovine colostrum preparation, IMMULAC™ (New Zealand Dairy Group, Cambridge, New Zealand), contains antibodies against various bacterial antigens. In the present study, we investigated the protective effects of a commercial bovine colostrum preparation against infections with enterohaemorrhagic Escherichia coli (EHEC) O157:H7 in a murine model. Balb/c mice were given drinking water containing streptomycin for 3 days before and following oral challenge with streptomycin‐resistant EHEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Bacterial ghosts provide all surface antigens in their natural conformations (12,20), and because of the induced immune response after immunization with EHEC O157:H7 ghosts, it can be assumed that the adherence of the challenge bacteria to the target cells (16,29,31) has been hampered by the induction of antibodies against surface antigens. Antibodies against surface antigens, like intimin, EspA, EspB, Tir, and lipopolysaccharide (LPS), were previously detected in humans after EHEC infections (6,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial ghosts provide all surface antigens in their natural conformations (12,20), and because of the induced immune response after immunization with EHEC O157:H7 ghosts, it can be assumed that the adherence of the challenge bacteria to the target cells (16,29,31) has been hampered by the induction of antibodies against surface antigens. Antibodies against surface antigens, like intimin, EspA, EspB, Tir, and lipopolysaccharide (LPS), were previously detected in humans after EHEC infections (6,29).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of an EHEC vaccine into a combination with other diarrheal vaccines for humans would be of great benefit to counter bioterrorism and to help prevent the spread of the disease in children and the elderly. Presently, several candidate vaccines against EHEC are under development (7,52) and have been tested in mouse models (16,23,28,44). It is believed that a vaccine that inhibits the organism from colonizing the intestinal tracts of both cattle and humans reflects the most promising way to prevent the infection (16,29,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Funatogawa et al 27 reported that immunoglobulinenriched bovine colostrum exhibited efficacy against E. coli O157:H7 by inhibiting attachment to the intestinal mucous membrane. VT levels in sera and in feces were not estimated in this study, and nor were the mechanisms by which this antibody reduces VT toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the overuse of antibiotics has already given rise to antibiotic-resistant strains during the past decades (Wilkerson et al, 2004;Fincher et al, 2009). Hence, there is growing interest in developing new alternatives to control STEC O157 : H7 infections (Isogai et al, 1998;Sugita-Konishi et al, 1999;Funatogawa et al, 2002;Gagnon et al, 2006;Babiuk et al, 2008;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%